What Hajj Teaches Global Governance - Syamsu Hidayat; Kurniawan Arif Maspul (Pubmedia Social Sciences and Humanities, 2026)
At a time of rising geopolitical tension, climate uncertainty, and declining global trust, Islamic civilisation is often misunderstood as either a historical legacy or a source of conflict. This study challenges those perceptions by showing that Islam remains a dynamic civilisational force shaping governance, finance, diplomacy, security, and environmental stewardship across the modern world. Drawing on classical Islamic sources, academic research, United Nations reports, think-tank analyses, and government documents, it examines how principles such as justice (ʿadl), consultation (shūrā), stewardship (khalīfah), and public welfare (maṣlaḥah) continue to shape contemporary policy and international engagement. The study argues that Islamic civilisation offers practical responses to twenty-first-century challenges through four interconnected dimensions: the modernisation of Hajj governance through advanced technologies, the growing influence of religious soft power in international relations, the resilience and ethical foundations of Islamic finance, and the role of faith-based values in promoting sustainability and conflict resolution. It introduces the concept of strategic entanglement to explain the interplay among religious norms, technological innovation, and geopolitical interests. Ultimately, the research contends that understanding Islam’s constructive civilisational capacity is not merely an academic exercise but a strategic necessity for policymakers seeking pathways towards peace, resilience, and a more inclusive global order in an increasingly fragmented world.